2013
DOI: 10.1371/journal.pone.0063855
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Low-Protein Diet Affects Epigenetic Regulation of Hepatic Mitochondrial DNA Transcription in a Sex-Specific Manner in Newborn Piglets Associated with GR Binding to Its Promoter

Abstract: Mitochondrial oxidative phosphorylation (OXPHOS) plays an important role in energy homeostasis by controlling electron transfer and ATP generation. Maternal malnutrition during pregnancy affects mitochondrial (mt) DNA-encoded OXPHOS activity in offspring, yet it is unknown whether epigenetic mechanism is involved in the transcriptional regulation of mtDNA-encoded OXPHOS genes. In this study, 14 primiparous purebred Meishan sows were fed either standard- (SP, 12% crude protein) or low-protein (LP; 6% crude prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 64 publications
4
37
0
Order By: Relevance
“…Significantly lower ruminal pH was observed in HC goats compared with LC goats, which was accompanied with greater VFA concentrations in ruminal fluids. These results were consistent with our previous studies (Dong et al, 2013;Jia et al, 2014;Tao et al, 2014;Tao et al, 2015). In those studies SARA were experimentally induced by feeding 65% concentrate diet for 2 months.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Significantly lower ruminal pH was observed in HC goats compared with LC goats, which was accompanied with greater VFA concentrations in ruminal fluids. These results were consistent with our previous studies (Dong et al, 2013;Jia et al, 2014;Tao et al, 2014;Tao et al, 2015). In those studies SARA were experimentally induced by feeding 65% concentrate diet for 2 months.…”
Section: Discussionsupporting
confidence: 93%
“…Cholesterol and TG were measured by commercial kits (E1015, E1013, respectively; Applygen Technologies Inc., Beijing, China) following the manufacturer's instructions. Concentrations of AMP, ADP, ATP, NAD and NADH in the liver were determined as described by Jia et al (2013). These parameters were analyzed by HPLC.…”
Section: Milk Compositionmentioning
confidence: 99%
“…Measurement of ATP, ADP, AMP, NAD and NADH levels in longissimus dorsi muscle The measurement of AMP, ADP, ATP, NAD and NADH concentrations in muscle were performed as previously described (Jia et al, 2013). A total of 50 ÎŒg of frozen muscle sample were extracted using 1 ml lysate which containing 0.6 M perchloric acid and 1 mM EDTA.…”
Section: Ethics Statementmentioning
confidence: 99%
“…It has been confirmed that GR is involved in the inflammatory response and plays an anti-inflammatory role [16,17]. GR was previously shown to translocate into the mitochondria and bind to the glucocorticoid response elements located in the mtDNA D-loop region [18,19], thereby exerting measurable effects on mitochondrial function [20]. However, the participation of GR in the LAmediated hepatic mitochondrial function effects during inflammation has never been investigated.…”
Section: Introductionmentioning
confidence: 99%